2015
DOI: 10.1002/gps.4299
|View full text |Cite
|
Sign up to set email alerts
|

Completed suicide among nursing home residents: a systematic review

Abstract: There is a paucity of research describing completed suicide among nursing home residents. More large-scale research is required using standardized methods for reporting information to better understand and prevent completed suicides in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 37 publications
6
43
0
1
Order By: Relevance
“…For example, this research found 50% of residents who died from suicide had resided in the nursing home for less than 12 months. This is consistent with the aggregate results from a recent systematic review, despite earlier mixed findings . Furthermore, over one‐third of residents in this study had previously attempted suicide.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, this research found 50% of residents who died from suicide had resided in the nursing home for less than 12 months. This is consistent with the aggregate results from a recent systematic review, despite earlier mixed findings . Furthermore, over one‐third of residents in this study had previously attempted suicide.…”
Section: Discussionsupporting
confidence: 92%
“…Prevention efforts may be better focused on improving the overall atmosphere and conditions of the nursing home to improve residents' quality of life . Location and time of suicides in nursing homes have not previously been described but have implications for nursing home policy and procedures. A large proportion of suicides occurred in the resident's bedroom and in the afternoon or evening hours, and 1 quarter of residents died from suicide while on day leave or extended leave away from the nursing home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, simply moving to a nursing home has been identified as a risk factor for suicide (Murphy et al . ). Nevertheless, little is known about the suicide situation among Chinese rural institutional elderly.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, social risk factors are associated with higher rates of suicide in older men, which suggests that more aggressive screening and treatment may be required. [21][22][23] The extent to which evidence about sex and gender is integrated into clinical practice guidelines for diagnosis and management of diseases remains unknown. We conducted a systematic review to investigate the integration of sex and gender evidence into Canadian clinical practice guidelines published between 2013 and 2015 for noncommunicable health conditions.…”
mentioning
confidence: 99%